2003
DOI: 10.1007/s10286-003-1110-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific complications and mortality of endoscopic thoracic sympathectomy

Abstract: Endoscopic Thoracic Sympathectomy (ETS) has gained an increasing popularity due to its minimal invasive character. Despite the simplicity of the procedure, non-surgical options should always be considered as the first line of treatment. The complication risk of ETS is low but side effects, primarily compensatory sweating (CS) of mainly the trunk may be severe enough to cause regret of the procedure. The risk/benefit ratio should always be discussed with the patient. Severe palmar hyperhidrosis and facial blush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
3
12
0
1
Order By: Relevance
“…We have found that this is a safe procedure with low-complication rates, and this has also been found by other centers [4,6,18]. Compensatory hyperhidrosis is the most frequent problem related to VATS [27].…”
Section: Discussionsupporting
confidence: 48%
“…We have found that this is a safe procedure with low-complication rates, and this has also been found by other centers [4,6,18]. Compensatory hyperhidrosis is the most frequent problem related to VATS [27].…”
Section: Discussionsupporting
confidence: 48%
“…However, one should bear in mind that although only anecdotally reported, several deaths have occurred due to sympathectomies [65,66]. At our institution, thoracoscopic sympathectomy has been performed since 1965 and roughly 1200 procedures have been performed in 600 patients.…”
Section: Discussionmentioning
confidence: 94%
“…Despite these low complication rates, which have been reported to be very similar by other authors, one has to bear in mind that they usually come from single centers with large experience. No mortality has been reported in these series, but from personal communications and medicolegal trials Cameron has collected information on 8 deaths [4], 4 of which were due to intraoperative hemorrhage and 3 related to anesthesia and ventilation problems.…”
Section: Complication Ratementioning
confidence: 98%